“Double-Hit” Chronic Lymphocytic Leukemia, Involving the TP53 and MYC Genes - Nguyen-Khac, Florence (Frontiers in Oncology, 2022)
Although the 17p deletion [del(17p)] is rare in cases of treatment-naive chronic lymphocytic leukemia (CLL), its frequency is higher in refractory/relapsed CLL – particularly in patients undergoing chemo(immuno)therapy. TP53 disruption (deletion and/or mutation) is the strongest prognostic factor for refractoriness to chemotherapy; the use of Bruton tyrosine kinase inhibitors and BCL2 inhibitors is then indicated. Rare cases of CLL can also harbor translocation or gain of the MYC oncogene. “Double-hit CLL” (with del(17p) and MYC gain) is associated with a very poor prognosis. The prognostic impact of TP53 disruption with MYC aberrations in patients receiving targeted therapies must now be evaluated.